Echocardiographic evidence for valvular toxicity of benfluorex: a double-blind randomised trial in patients with type 2 diabetes mellitus. - Geneviève Derumeaux; Laura Ernande; André Serusclat; Evelyne Servan; Eric Bruckert; Hugues Rousset; Stephen Senn; Luc Van Gaal; Brigitte Picandet; François Gavini; Philippe Moulin; REGULATE trial investigators (PLoS ONE)
Objectives REGULATE trial was designed to compare the efficacy and safety of benfluorex versus pioglitazone in type 2 diabetes mellitus (DM) patients. Methods Double-blind, parallel-group, international, randomised, non-inferiority trial. More than half of the 196 participating centres were primary care centres. Patients eligible had type 2 DM uncontrolled on sulfonylurea. 846 were randomised. They received study treatment for 1 year. 423 patients were allocated to benfluorex (150 to 450 mg/day) and 423 were allocated to pioglitazone (30 to 45 mg/day). Primary efficacy criterion was HbA(1c). Safety assessment included blinded echocardiographic evaluation of cardiac and valvular status. Results At baseline, patients were 59.1 ± 10.5 years old with HbA1c 8.3 ± 0.8%, and DM duration 7.1 ± 6.0 years. During the study, mean HbA1c significantly decreased in both groups (benfluorex: from 8.30 ± 0.80 to 7.77 ± 1.31 versus pioglitazone: from 8.30 ± 0.80 to 7.45 ± 1.30%). The last HbA1c value was significantly lower with pioglitazone than with benfluorex (p<0.001) and non-inferiority of benfluorex was not confirmed (p = 0.19). Among the 615 patients with assessable paired echocardiography (310 benfluorex, 305 pioglitazone), 314 (51%) had at least one morphological valvular abnormality and 515 (84%) at least one functional valvular abnormality at baseline. Emergent morphological abnormalities occurred in 8 patients with benfluorex versus 4 with pioglitazone (OR 1.99), 95% CI (0.59 to 6.69). Emergent regurgitation (new or increased by one grade or more) occurred more frequently with benfluorex (82 patients, 27%) than with pioglitazone (33 patients, 11%) (OR 2.97), 95% CI (1.91 to 4.63) and were mainly rated grade 1; grade 2 (mild) was detected in 2 patients with benfluorex and 3 with pioglitazone. There was no moderate or severe regurgitation. Conclusion After 1 year of exposure, our results show a 2.97 fold increase in the incidence of valvular regurgitation with benfluorex and provide evidence for the valvular toxicity of this drug.